Hypoxia-stressed cardiomyocytes promote early cardiac differentiation of cardiac stem cells through HIF-1α/Jagged1/Notch1 signaling - Keke Wang; Ranran Ding; Yanping Ha; Yanan Jia; Xiaomin Liao; Sisi Wang; Rujia Li; Zhihua Shen; Hui Xiong; Junli Guo; Wei Jie (Elsevier, 2018)
Hypoxia is beneficial for the differentiation of stem cells transplanted for myocardial injury, but mechanisms underlying this benefit remain unsolved. Here, we report the impact of hypoxia-induced Jagged1 expression in cardiomyocytes (CMs) for driving the differentiation of cardiac stem cells (CSCs). Forced hypoxia-inducible factor 1α (HIF-1α) expression and physical hypoxia (5% O2) treatment could induce Jagged1 expression in neonatal rat CMs. Pharmacological inhibition of HIF-1α by YC-1 attenuated hypoxia-promoted Jagged1 expression in CMs. An ERK inhibitor (PD98059), but not inhibitors of JNK (SP600125), Notch (DAPT), NF-κB (PTDC), JAK (AG490), or STAT3 (Stattic) suppressed hypoxia-induced Jagged1 protein expression in CMs. c-Kit+ CSCs isolated from neonatal rat hearts using a magnetic-activated cell sorting method expressed GATA4, SM22α or vWF, but not Nkx2.5 and cTnI. Moreover, 87.3% of freshly isolated CSCs displayed Notch1 receptor expression. Direct co-culture of CMs with BrdU-labeled CSCs enhanced CSCs differentiation, as evidenced by an increased number of BrdU+/Nkx2.5+ cells, while intermittent hypoxia for 21 days promoted co-culture-triggered differentiation of CSCs into CM-like cells. Notably, YC-1 and DAPT attenuated hypoxia-induced differentiation. Our results suggest that hypoxia induces Jagged1 expression in CMs primarily through ERK signaling, and facilitates early cardiac lineage differentiation of CSCs in CM/CSC co-cultures via HIF-1α/Jagged1/Notch signaling. KEY WORDS: Cardiac stem cell, Cardiomyocyte, Co-culture, Hypoxia, Notch1 signaling, Cell differentiation